1995
DOI: 10.1111/j.1348-0421.1995.tb03267.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth Conditions Influence Expression of Cell Surface Hydrophobicity of Staphylococci and Other Wound Infection Pathogens

Abstract: The initial adhesion of microbes to tissue and solid surfaces can be mediated by hydrophobic interaction. Expression of microbial cell surface hydrophobicity (CSH) is influenced by growth conditions, and often best expressed after growth under nutrient-poor conditions, or "starvation." In the present study, the CSH of 133 strains of Enterobacteriaceae, Staphylococcus aureus, coagulase-negative staphylococci, Enterococcus faecalis, group A streptococcus, Pseudomonas aeruginosa, Clostridium perfringens, Bacteroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…From the results of hydrophobicity at both temperatures determined by the MATH method (Table 2), it was found that hydrophobicity increased with respect to the control sample when the culture medium was supplemented with serum and decreased if supplemented with urine. This behaviour is similar to that described by water contact angles (Table 4) at 37 ± C but not at 22 ± C. The effect of serum on the hydrophobicity of the cell surface of enterococci is in agreement with the results obtained by Ljungh and Wadstrom [23] when determining the hydrophobicity of different microorganisms (among them E. faecalis) grown with serum. Nevertheless, these authors could not attribute the phenomenon to a speci c serum component.…”
Section: In Uence Of the Growth Medium On Hydrophobicity Zeta Potentsupporting
confidence: 88%
“…From the results of hydrophobicity at both temperatures determined by the MATH method (Table 2), it was found that hydrophobicity increased with respect to the control sample when the culture medium was supplemented with serum and decreased if supplemented with urine. This behaviour is similar to that described by water contact angles (Table 4) at 37 ± C but not at 22 ± C. The effect of serum on the hydrophobicity of the cell surface of enterococci is in agreement with the results obtained by Ljungh and Wadstrom [23] when determining the hydrophobicity of different microorganisms (among them E. faecalis) grown with serum. Nevertheless, these authors could not attribute the phenomenon to a speci c serum component.…”
Section: In Uence Of the Growth Medium On Hydrophobicity Zeta Potentsupporting
confidence: 88%
“…Generally, bacteria grown on solid media bound rvWF to a greater extent than after growth in liquid media. Nutrient-poor conditions, which promote microbial adhesion to tissue or solid surfaces, did not enhance binding of all species [35]. In the present study 14 Staphylococcus strains, including reference strains, were tested for binding of soluble rvWF, and they all bound rvWF to varying extents.…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria concentration in the standard solution was maintained at around 10 8 bacteria/mL. 30 The collagen-bonding samples were incubated with the bacteria solution for 30 min, and then those samples were exposed under varied gamma ray exposure doses. After gamma ray irradiation, the samples were incubated under a controlled atmosphere and observed after 24 h to evaluate their colony formation.…”
Section: Sterilization Testmentioning
confidence: 99%